Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Molecular Doping of PCPDT–BT Copolymers: Comparison of Molecular Complexes with and without Integer Charge Transfer - Dong, Chuan-Ding; Schumacher, Stefan (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

Controlling the Electronic Contact at the Terpyridine/Metal Interface - Mennicken, Max; Peter, Sophia Katharina; Kaulen, Corinna; Simon, Ulrich; Karthäuser, Silvia (The Journal of Physical Chemistry C)
Keywords: pc2-ressources

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas D.; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)

Stepwise Growth of Ruthenium Terpyridine Complexes on Au Surfaces - Peter, Sophia Katharina; Kaulen, Corinna; Hoffmann, Alexander; Ogieglo, Wojciech; Karthäuser, Silvia; Homberger, Melanie; Herres-Pawlis, Sonja; Simon, Ulrich (The Journal of Physical Chemistry C)

Vibrational Properties of RbInSe2: Raman Scattering Spectroscopy and First-Principle Calculations - Guc, Maxim; Kodalle, Tim; Kormath Madam Raghupathy, Ramya; Mirhosseini, Hossein; Kühne, Thomas; Becerril-Romero, Ignacio; Pérez-Rodríguez, Alejandro; Kaufmann, Christian A.; Izquierdo-Roca, Victor (The Journal of Physical Chemistry C)
RbInSe2 is attracting growing interest as a secondary semiconductor compound in Cu(In,Ga)Se2-based solar cells by virtue of the recent investigations on absorber post-deposition treatments with alkali metal salts that have resulted in significant efficiency improvements. However, the detection of the RbInSe2 phase on the surface of chalcopyrite absorbers is very challenging due to its nanometric thickness and the limited information available about its fundamental properties. In this context, this work expounds a detailed analysis of the vibrational properties of RbInSe2 that combines first-principle calculations with multiwavelength Raman scattering spectroscopy and provides a methodology for the detection and identification of very thin layers of this material employing solely optical measurements. As a result, here, we present the classification of the different vibrational modes together with the fingerprint Raman spectra of RbInSe2 thin films measured under five different excitations (close to and far from resonance). The employment of a 442 nm excitation wavelength is found to be the most adequate strategy for the detection and characterization of the RbInSe2 phase in view of its resonance with the band gap of the material and its low penetration depth. Additionally, the purity of the deposited thin films as well as the possible influence of the subjacent layers on the Raman spectra of the compound are also investigated by analyzing the presence of secondary phases and by measuring RbInSe2 thin films deposited onto Mo-coated soda-lime glass, respectively. These results set the basis for the future evaluation of the suitability of Raman spectroscopy as a fast and nondestructive characterization technique for the reliable identification and characterization of the nanometric layers of RbInSe2 in Cu(In,Ga)Se2-based solar cells.

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Curved Polar Dibenzocoronene Esters and Imides versus Their Planar Centrosymmetric Homologs: Photophysical and Optoelectronic Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Phase Transitions of Ice in Aqueous Salt Solutions within Nanometer-Sized Pores - Jantsch, Evelyn; Weinberger, Christian; Tiemann, Michael; Koop, Thomas (The Journal of Physical Chemistry C)
We examined the effect of CaCl2 and LiCl on ice melting in mesoporous silica (MCM-41 and SBA-15 silica). For that purpose, we determined the ice melting temperature in pores of various size (pore radii between 1.9 and 11.1 nm) in water and aqueous solutions up to high total solute molality (up to about 12 mol kg–1) using differential scanning calorimetry. We found that both electrolytes reduce the ice melting temperature within the pores. An exception is the melting of ice in the smallest pores, which does not seem to be affected by the presence of solutes, most likely owing to an exclusion of the ions from entering the pores. For all other pores, we observed that the ice melting temperature decreases as a function of pore size and electrolyte concentration. Using thermodynamic considerations as well as additional experimental data we developed a parametrization that can be used to predict the ice melting point as a function of pore size and total solute molality. For that purpose, we extended a formulation of the effective water activity of aqueous solutions under mechanical pressure toward its application in confinement and tested this new parametrization on literature data.

Enhanced Stability of Single-Layer w-Gallenene through Hydrogenation - Badalov, S. V.; Yagmurcukardes, M.; Peeters, F. M.; Sahin, H. (The Journal of Physical Chemistry C)

Switchable Plasmonic Holograms Utilizing the Electro-Optic Effect of a Liquid-Crystal Circular Polarizer - Atorf, Bernhard; Rasouli, Hoda; Mühlenbernd, Holger; Reineke, Bernhard J.; Zentgraf, Thomas; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Dependencies of the Adhesion Forces between TiO2 Nanoparticles on Size and Ambient Humidity - Laube, Jens; Dörmann, Michael; Schmid, Hans-Joachim; Mädler, Lutz; Colombi Ciacchi, Lucio (The Journal of Physical Chemistry C)
We study the variation of the adhesion forces between wet TiO2 nanoparticles as a function of their size and the ambient relative humidity. Combining all-atom molecular dynamics and capillary simulations we demonstrate that the linear scaling of the interparticle forces with the particle diameter, well established for microscopic and macroscopic particles, can be extended down to diameters of a few nm. At this size scale, however, the molecular nature of the water adsorbates dictates the adhesion forces both via solvation effects and influencing parameters of analytical capillary models such as the equilibrium particle–particle separation distance and the water/particle contact angle. Moreover, the water surface tension becomes considerably larger than the macroscopic bulk value due to combined effects of thin-film confinement and tight curvature, in a way that strongly depends on humidity and particle size. Taking these effects into proper account, classical capillary equations can be used to predict the interparticle forces even of the smallest particles considered here (4 nm), although the circular approximation fails to reproduce the distance at which the water meniscus breaks. Finally, the transition between the dominating effects at the nanoscopic scale and conventional capillary theory valid at microscopic size scales can be only rationalized if the presence of roughness asperities on the surface of the large particles is explicitly taken into account.

X-ray Spectroscopy of Thin Film Free-Base Corroles: A Combined Theoretical and Experimental Characterization - Aldahhak, Hazem; Paszkiewicz, M.; Allegretti, F.; Duncan, D. A.; Tebi, S.; Deimel, P. S.; Casado Aguilar, P.; Zhang, Y.-Q.; Papageorgiou, A. C.; Koch, R.; Barth, J. V.; Schmidt, Wolf Gero; et al. (The Journal of Physical Chemistry C)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Insights into Intrinsic Defects and the Incorporation of Na and K in the Cu2ZnSnSe4 Thin-Film Solar Cell Material from Hybrid-Functional Calculations - Ghorbani, Elaheh; Kiss, Janos; Mirhosseini, Hossein; Schmidt, Markus; Windeln, Johannes; Kühne, Thomas; Felser, Claudia (The Journal of Physical Chemistry C)

Inhomogeneous and Homogeneous Line Broadening of Optical Spectra of PTCDA Molecules Adsorbed at Step Edges of Alkali Halide Surfaces - Paulheim, A.; Marquardt, C.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero; Sokolowski, M. (The Journal of Physical Chemistry C)

Bay-Extended, Distorted Perylene Esters Showing Visible Luminescence after Ultraviolet Excitation: Photophysical and Electrochemical Analysis - Vollbrecht, Joachim; Wiebeler, Christian; Neuba, Adam; Bock, Harald; Schumacher, Stefan; Kitzerow, Heinz-Siegfried (The Journal of Physical Chemistry C)

Order and Melting in Self-Assembled Alkanol Monolayers on Amorphous SiO2 - Haddad, Julia; Steinrück, Hans-Georg; Hlaing, Htay; Kewalramani, Sumit; Pontoni, Diego; Reichert, Harald; Murphy, Bridget M.; Festersen, Sven; Runge, Benjamin; Magnussen, Olaf M.; Magerl, Andreas; Deutsch, Moshe; et al. (The Journal of Physical Chemistry C)

Hybrid-Functional Calculations on the Incorporation of Na and K Impurities into the CuInSe2 and CuIn5Se8 Solar-Cell Materials - Ghorbani, Elaheh; Kiss, Janos; Mirhosseini, Hossein; Roma, Guido; Schmidt, Markus; Windeln, Johannes; Kühne, Thomas; Felser, Claudia (The Journal of Physical Chemistry C)

Subpicosecond Exciton Dynamics in Polyfluorene Films from Experiment and Microscopic Theory - Denis, Jean-Christophe; Schumacher, Stefan; Hedley, Gordon J.; Ruseckas, Arvydas; Morawska, Paulina O.; Wang, Yue; Allard, Sybille; Scherf, Ullrich; Turnbull, Graham A.; Samuel, Ifor D. W.; Galbraith, Ian (The Journal of Physical Chemistry C)

Liquid Crystal (8CB) Molecular Adsorption on Lithium Niobate Z-Cut Surfaces - Braun, Christian; Sanna, Simone; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Nanopatterning on H-Terminated Si(111) Explained as Dynamic Equilibrium of the Chemical Reaction with Methanol - Thissen, Peter; Fuchs, Ehud; Roodenko, Katy; Peixoto, Tatiana; Batchelor, Ben; Smith, Dennis; Schmidt, Wolf Gero; Chabal, Yves (The Journal of Physical Chemistry C)

Modeling LiNbO3 Surfaces at Ambient Conditions - Hölscher, Rebecca; Schmidt, Wolf Gero; Sanna, Simone (The Journal of Physical Chemistry C)

Adsorption of PTCDA on Terraces and at Steps Sites of the KCl(100) Surface - Guo, Q.; Paulheim, A.; Sokolowski, M.; Aldahhak, Hazem; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Formation of Hydroxyl Groups at Calcium-Silicate-Hydrate (C-S-H): Coexistence of Ca–OH and Si–OH on Wollastonite(001) - Sanna, Simone; Schmidt, Wolf Gero; Thissen, Peter (The Journal of Physical Chemistry C)

Excited-State Absorption of Conjugated Polymers in the Near-Infrared and Visible: A Computational Study of Oligofluorenes - Ling, Sanliang; Schumacher, Stefan; Galbraith, Ian; Paterson, Martin J. (The Journal of Physical Chemistry C)

Nanostructure-Related Magnetic Properties of Various Mesoporous Cobalt Oxide and Cobalt Ferrite Spinel Phases - Haffer, Stefanie; Walther, Till; Köferstein, Roberto; Ebbinghaus, Stefan G.; Tiemann, Michael (The Journal of Physical Chemistry C)
Nanostructure-related magnetic properties are investigated systematically for various mesoporous cobalt oxide (Co3O4) and cobalt ferrite (CoFe2O4) spinel phases. Synthesis of the materials by nanocasting offers the opportunity to obtain materials which are different from each other with respect to both specific surface area and crystallite size. As a result, the respective contributions of two types of interfaces, namely, “solid–gas” and “solid–solid” interfaces, to the magnetic ordering can be distinguished. Structural characterization of the porous materials by X-ray diffraction, N2 physisorption, and electron microscopy as well as investigation of the magnetic behavior (field-dependent magnetization and temperature-dependent susceptibility) are presented.

Substrate Induced Thermal Decomposition of Perfluoro-Pentacene Thin Films on the Coinage Metals - Schmidt, Christian; Breuer, Tobias; Wippermann, Stefan; Schmidt, Wolf Gero; Witte, Gregor (The Journal of Physical Chemistry C)

Structure–Activity Studies on Highly Active Palladium Hydrogenation Catalysts by X-ray Absorption Spectroscopy - Bauer, Matthias; Schoch, Roland; Shao, Lidong; Zhang, Bingsen; Knop-Gericke, Axel; Willinger, Marc; Schlögl, Robert; Teschner, Detre (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Modulated Formation of MOF-5 Nanoparticles—A SANS Analysis - Nayuk, R.; Zacher, D.; Schweins, R.; Wiktor, C.; Fischer, R. A.; van Tendeloo, G.; Huber, Klaus (The Journal of Physical Chemistry C)
Keywords: Surfaces; Coatings and Films; Physical and Theoretical Chemistry; General Energy; Electronic; Optical and Magnetic Materials

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Photoluminescence Properties of Ordered Mesoporous ZnO - Chernikov, Alexej; Horst, Swantje; Waitz, Thomas; Tiemann, Michael; Chatterjee, Sangam (The Journal of Physical Chemistry C)
Nanoporous ZnO powders with high surface-to-mass ratios (SMR) between 15 and 70 m2 g−1 are synthesized, structurally characterized, and studied by time-resolved photoluminescence (PL). A strong dependence of the recombination dynamics and spectral width on SMR is observed at T = 10 K, and pronounced disorder-induced effects are found in the temperature dependence. Both the thermally induced shift of the PL maximum and the spectrally integrated PL intensity are interpreted by appropriate theoretical models. This consistent quantitative analysis of the experimental data yields a characteristic energy of 15 meV for the disorder scale in the nanoporous ZnO sample with an intermediate SMR.

Mesoporous In2O3 with Regular Morphology by Nanocasting: A Simple Relation between Defined Particle Shape and Growth Mechanism - Haffer, Stefanie; Waitz, Thomas; Tiemann, Michael (The Journal of Physical Chemistry C)
In2O3 with ordered, uniform mesoporosity is prepared by nanocasting, using various porous silica phases (KIT-6, SBA-15) as structure matrices. The In2O3 particles exhibit well-defined morphologies (spherical or ellipsoidal, depending on the choice of silica matrix) and quite uniform sizes in the range of a few hundred nanometers. The regular morphology of the In2O3 particles is not associated with the morphological properties of the silica matrices. Instead, it is the result of the growth mechanism of In2O3 inside the silica pores; this mechanism is investigated in some detail. Hence, the nanocasting method offers a versatile and simple way of creating mesoporous In2O3 with regular morphology; this will be beneficial for many applications that require well-defined morphological properties, such as gas sensing or catalysis.

Role of Dihydrogen Bonds for the Stabilization of Self-Assembled Molecular Nanostructures - Blankenburg, S.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Chainlike Au−O Structures on Au(110)-(1 × r) Surfaces Calculated from First Principles - Landmann, M.; Rauls, E.; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

Ripening Effects in ZnS Nanoparticle Growth - Tiemann, Michael; Marlow, Frank; Hartikainen, Juha; Weiss, Özlem; Lindén, Mika (The Journal of Physical Chemistry C)
The growth of ZnS nanoparticles during precipitation from aqueous solution is studied by in situ stopped-flow UV absorption spectroscopy at temperatures between 283 and 323 K. Particle growth is marked by substantial ripening during the first 60 ms. Kinetic data suggest that a ripening mechanism by coalescence (oriented attachment) is predominant over Ostwald ripening, although the latter seems to coexist to a significant degree at early temporal stages, predominantly at low temperatures.

The Influence of Catalyst's Oxidation Degree on Carbon Nanotube Growth as a Substrate-Independent Parameter - de los Arcos de Pedro, Maria Teresa; Oelhafen, Peter; Thommen, Verena; Mathys, Daniel (The Journal of Physical Chemistry C)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)